Government Spending, Public Debt and Economic Growth in Kenya - Kipruto, Chemwok Christopher; Siele, Richard K.; Saina, Ernest K. (Research Parks Publishers, 2023)
Kenya economic growth has been declining despite the huge government spending and appetite for borrowing. Recently, the ratio of Kenya’s debt to GDP was 63.0% in December 2022, 13.0% more than the IMF’s suggested level of 50.0% for a middle level income economy. This paper highlighted how these two variables have influenced economic growth. Results indicate a negative impact and Kenyan government need to be extra cautious on borrowing because a debt crisis can result in significant losses for domestic and foreign banks, potentially jeopardizing the viability of financial systems both in the crisis-hit nation and beyond. This may hinder economic expansion and wreak havoc on international financial markets. The paper recommends that the proceeds from the borrowed money be used to finance government spending that will benefit the economy of the nation.